2000
DOI: 10.1038/sj.cgt.7700126
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human breast cancer cells with antisense RNA to the type I insulin-like growth factor receptor inhibits cell growth, suppresses tumorigenesis, alters the metastatic potential, and prolongs survival in vivo

Abstract: The type I insulin-like growth factor receptor (IGF-IR) plays an important role in the growth and transformation of breast cancer cells. In this study, we investigated the effects of treatment with an antisense IGF-IR construct on cells from the highly metastatic estrogen receptor-negative human breast cancer cell line MDA-MB-435s. The cells carrying the antisense IGF-IR had a markedly reduced expression of IGF-IR, had a significant decrease in cell proliferation, and lost the ability to form colonies in soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…Another potential problem is the substantial selection pressure against the expression of a growth inhibitory gene, which may render its expression unstable. Cell lines appear to vary in this respect: constitutive expression of AS-IGF1R RNA by neuroblastoma and prostate cancer cells was rapidly lost (Burfeind et al, 1996;Whitesell et al, 1999), but was stably retained by breast cancer cells (Chernicky et al, 2000). We found that the AS-IGF1R phenotype was expressed by B16 clones for months but could be lost unpredictably, emphasising the need for repeated phenotype checks.…”
Section: Igf1r Downregulation Enhances the Radiosensitivity Of Melanomentioning
confidence: 63%
See 1 more Smart Citation
“…Another potential problem is the substantial selection pressure against the expression of a growth inhibitory gene, which may render its expression unstable. Cell lines appear to vary in this respect: constitutive expression of AS-IGF1R RNA by neuroblastoma and prostate cancer cells was rapidly lost (Burfeind et al, 1996;Whitesell et al, 1999), but was stably retained by breast cancer cells (Chernicky et al, 2000). We found that the AS-IGF1R phenotype was expressed by B16 clones for months but could be lost unpredictably, emphasising the need for repeated phenotype checks.…”
Section: Igf1r Downregulation Enhances the Radiosensitivity Of Melanomentioning
confidence: 63%
“…IGF1R expression or function can be blocked using antisense RNA or oligonucleotides, or dominant negative IGF1R mutants. These approaches have been shown to inhibit in vivo growth of tumours including breast, prostate, and lung cancer, melanoma, hepatoma, neuroblastoma and glioblastoma (Resnico et al, 1994a,b;Burfeind et al, 1996;Lee et al, 1996;Liu et al, 1998;Chernicky et al, 2000;Khandwala et al, 2000;Wang et al, 2000). Thus it is clear that the IGF1R mediates many aspects of the malignant phenotype, and represents a highly promising therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, stable expression of type I IGF-IR antisense RNA by using a plasmid vector resulted in a significant decrease in IGF-I and serumstimulated growth in MCF-7 human breast cancer cells (Neuenschwander et al, 1995). In addition, recent findings demonstrated that transfection of the highly metastatic, ER negative, MDA-MB-435s breast cancer cell line with a construct carrying antisense IGF-IR RNA resulted in a significant reduction of cell proliferation and loss of soft agar growth (Chernicky et al, 2000). Moreover, there was suppression of tumorigenesis, reduction in the metastatic potential and prolonged survival after injection of MDA-MB-435 s cells expressing antisense IGF-IR into the mammary fat pads of immune compromised mice (Chernicky et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…These include agents that reduce ligand availability such as anti-IGF antibodies, anti-sense, and RNA interference molecules to reduce IGF-IR expression and small molecule inhibitors that target IGF-IR tyrosine kinase activity. Pre-clinical studies performed in vitro and/or in nude mice using these strategies have demonstrated that targeting IGF-IR directly or indirectly can inhibit breast cancer cell growth (Arteaga et al, 1989;Chernicky et al, 2000;Burtrum et al, 2003;Mitsiades et al, 2004;Goetsch et al, 2005;Divisova et al, 2006;Feng et al, 2006;Haluska et al, 2007;Rowinsky et al, 2007). Although these experiments certainly illustrate the therapeutic potential of inhibiting IGF-IR, there are a number of limitations of these studies that should be considered.…”
Section: Introductionmentioning
confidence: 99%